Genome-Wide Association Study of Peripheral Arterial Disease in a Japanese Population - Matsukura, Mitsuru; Ozaki, Kouichi; Takahashi, Atsushi; Onouchi, Yoshihiro; Morizono, Takashi; Komai, Hiroyoshi; Shigematsu, Hiroshi; Kudo, Toshifumi; Inoue, Yoshinori; Kimura, Hideo; Hosaka, Akihiro; Shigematsu, Kunihiro; et al. (PLOS ONE, 2015)
Characteristics of peripheral arterial disease (PAD) are the occlusion or stenosis of multiple vessel sites caused mainly by atherosclerosis and chronic lower limb ischemia. To identify PAD susceptible loci, we conducted a genome-wide association study (GWAS) with 785 cases and 3,383 controls in a Japanese population using 431,666 single nucleotide polymorphisms (SNP). After staged analyses including a total of 3,164 cases and 20,134 controls, we identified 3 novel PAD susceptibility loci at IPO5/RAP2A, EDNRA and HDAC9 with genome wide significance (combined P = 6.8 x 10−14, 5.3 x 10−9 and 8.8 x 10−8, respectively). Fine-mapping at the IPO5/RAP2A locus revealed that rs9584669 conferred risk of PAD. Luciferase assay showed that the risk allele at this locus reduced expression levels of IPO5. To our knowledge, these are the first genetic risk factors for PAD.